Vaccines and vaccination in prison settings: availability and model of service delivery in 20 European countries - Moazen, Babak; Tramonti Fantozzi, Maria; De Vita, Erica; Petri, Davide; Barbîroș, Irina; Busmachiu, Vlad; Ranieri, Roberto; Cocco, Nicola; Mieuset, Aurélie; Meroueh, Fadi; Baglietto, Laura; Stöver, Heino; et al. (BMC public health, 2024)
Prisons, due to various risk factors, are environments that are conducive to infectious disease transmission, with significantly higher prevalence of infectious diseases within prisons compared to the general population. This underscores the importance of preventive measures, particularly vaccination. As part of the international project “Reaching the hard-to-reach: Increasing access and vaccine uptake among the prison population in Europe” (RISE-Vac), this study aimed to map the availability and delivery framework of vaccination services in prisons across Europe and beyond. A questionnaire designed to collect data on the availability and delivery model of vaccination services in prisons was validated and uploaded in SurveyMonkey in July 2023. Then, it was submitted to potential participants, with at least one representative from each European country. Potential participants emailed an invitation letter by the RISE-Vac partners and by the European Organization of Prison and Correctional Services (EUROPRIS). Twenty European countries responded. Vaccines are available in European countries, although their availability differs by country and type of vaccine. The first dose is offered to people living in prisons (PLP), mostly within one month, COVID-19 is the most widely offered vaccine. In all countries, vaccines are actively offered by healthcare workers; in most countries, there is no evaluation of vaccination status among people who work in prison. The survey shows variance in vaccine availability for PLP and staff across countries and vaccine types. Quality healthcare in prisons is not only a matter of the right to health but also a critical public health investment: enhancing vaccine uptake consistently among PLP and staff should be prioritized.
Gesehen am 17.06.2025